2014
DOI: 10.1007/s13197-014-1686-y
|View full text |Cite
|
Sign up to set email alerts
|

In vitro probiotic evaluation of phytase producing Lactobacillus species isolated from Uttapam batter and their application in soy milk fermentation

Abstract: Probiotic lactic acid bacteria are health promoters and have been traditionally consumed without the knowledge that they have beneficial properties. These bacteria mainly involve in secreting antimicrobials, enhance immune-modulatory effects, and preserve the intestinal epithelial barrier by competitively inhibiting the pathogenic organisms. The aim of this study was to investigate the in vitro probiotic properties of Lactobacillus pentosus, Lactobacillus plantarum, Lactobacillus plantarum ssp. argentoratensis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Many bacterial isolates have been identified to exhibit hypocholesterolemic activity through their effect on host by decreasing cholesterol levels in intestinal tract and preventing from coronary heart disease. Removal of cholesterol is carried through assimilation or de conjugation of bile acids promoting excretion or binding the cell surface of both dead and live cells of probiotic bacteria (Saraniya and Jeevaratnam 2015). In our study, considerable range of cholesterol removed in the medium was precipitated with inclusion of deconjugated bile acids (ox-bile).…”
Section: Discussionmentioning
confidence: 71%
“…Many bacterial isolates have been identified to exhibit hypocholesterolemic activity through their effect on host by decreasing cholesterol levels in intestinal tract and preventing from coronary heart disease. Removal of cholesterol is carried through assimilation or de conjugation of bile acids promoting excretion or binding the cell surface of both dead and live cells of probiotic bacteria (Saraniya and Jeevaratnam 2015). In our study, considerable range of cholesterol removed in the medium was precipitated with inclusion of deconjugated bile acids (ox-bile).…”
Section: Discussionmentioning
confidence: 71%
“…In present study phytase hydrolysis was checked on phytase screening medium as described previously (Aziz et al, 2015) while other studies have also used modified MRS agar with sodium phytate and wheat bran extract agar (Saraniya and Jeevaratnam, 2015). Approximately 68% isolates showed phytase like activity.…”
Section: Discussionmentioning
confidence: 97%
“…Several authors have reported that different strains of lactic acid bacteria have the ability to reduce the levels of phytates in food (Raghavendra & Halami, 2009;Fischer et al, 2014). Saraniya and Jeevaratnam (2014) reported that L. plantarum and L. pentosus decrease 47 and 66% the phytate content in soymilk fermented after 18 h compared to the unfermented soymilk. García-Mantrana et al (2015) reported that in soymilk fermented with L. casei the phytate content remained constant throughout fermentation.…”
Section: Phytate Content During Fermentation Of Soymilkmentioning
confidence: 99%